2017
DOI: 10.1097/pai.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Specific Diagnosis of Extrapulmonary Tuberculosis by Immunostaining of Tissues and Aspirates With Anti-MPT64

Abstract: Background: Extrapulmonary tuberculosis (EPTB) constitutes about 15% to 20% of all cases of tuberculosis (TB). The confirmation of EPTB has always been a challenge to laboratory personnel. We aim to evaluate the diagnostic potential of immunostaining with anti-MPT64 in various EPTB specimens. Materials and Methods:We studied a total of 51 TB cases and 38 non-TB control specimens comprising of fine-needle aspirates and formalin-fixed biopsies. These were investigated using a combination of the Ziehl-Neelsen met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…When a diagnostic validation of immunostaining was performed using PCR as the gold standard, the overall sensitivity, specificity, and positive and negative predictive values for immunostaining with anti-MPT64 were 100%, 97%, 98%, and 100%, respectively. (21) IHC for tuberculosis has, however, been slow to catch on as a routine diagnostic method in histopathology laboratories probably due to the lack of a specific anti-mycobacterial antibody suitable for all types of tissues and hence the exact diagnostic role of IHC for M. tuberculosis has to be assessed. Present study shows that IHC with anti-MPT64 has better specificity, sensitivity, and predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…When a diagnostic validation of immunostaining was performed using PCR as the gold standard, the overall sensitivity, specificity, and positive and negative predictive values for immunostaining with anti-MPT64 were 100%, 97%, 98%, and 100%, respectively. (21) IHC for tuberculosis has, however, been slow to catch on as a routine diagnostic method in histopathology laboratories probably due to the lack of a specific anti-mycobacterial antibody suitable for all types of tissues and hence the exact diagnostic role of IHC for M. tuberculosis has to be assessed. Present study shows that IHC with anti-MPT64 has better specificity, sensitivity, and predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and accurate TB diagnosis using pathogen markers remains a difficult goal. Detection of MPT64 and antigen 85B via immunostaining of tissues and fine-needle aspirates can be rapid and sensitive methods for establishing an early and specific diagnosis of TB infection but are limited to pathology and microbiology laboratories ( 42 , 43 ). Detection of MPT64 in sputum cultures utilizing an immune-chromatographic assay, in conjunction with cording in a stained smear, has been used to make a preliminary yet high-confidence identification of M. tuberculosis complex in liquid culture ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…MPT64 detection had the best performance in TB lymphadenitis patients and children with TB, suggesting that MPT64 detection could be used for routine diagnosis under low resource allocation to improve the diagnosis of extrapulmonary tuberculosis, especially for tuberculous lymphadenitis and children with TB [39] . Purohit et al studied 51 cases of pulmonary tuberculosis and 38 control specimens of non-pulmonary tuberculosis.The results suggested that anti-MPT64 immunostaining detection was a rapid and sensitive method for early specific diagnosis of Mycobacterium tuberculosis infection [40] . This technique can easily be incorporated into routine pathological laboratories.…”
Section: Detection Of Mtbc By Intestinal Tuberculosis Protein Combinementioning
confidence: 91%